Neuro-Linguistic Programming & VR via the 8 Pillars of Metacognition X 8 Layers of Consciousness X 8 Intelligences - Drigas, Athanasios; Mitsea, Eleni (Technium Social Sciences Journal, 2021)
Neuro-linguistic programming (NLP) has already achieved great popularity as a method for personal development and excellence. It is already used by successful educators, managers, trainers, salespeople, market researchers, counselors, consultants, medics, top athletes and lawyers. However, there is a lack of understanding about the secrets behind the success of neuro-linguistic training in various areas of human life. What are the pillars of its success? What is the role of metacognition? The specific aim of the present review is to explore the relationship between neuro-linguistic programming and metacognition as well as their role in building human excellence. In addition, we investigate, for the first time to our knowledge, the effectiveness of NLP in virtual reality in order to promote metacognitive development in terms of behavior change, subconscious reshaping and consciousness-raising. The results of this review showed that there is a mutually reinforcing relationship between Neuro-linguistic programming and Metacognition. Research has also shown that virtual reality provides the ideal environment for the application of subconscious training techniques like those of NLP. We conclude with a new layered model of NLP based on the principles of metacognition. This model aims to condition people to become awake, transcend their limitations, and enter a higher state of consciousness.